Treatment of large persistent tracheoesophageal peristomal fistulas using silicon rings - Ibrahim Erdim; Ali Ahmet Sirin; Bahadir Baykal; Fatih Oghan; Ali Guvey; Fatma Tulin Kayhan (Brazilian Journal of Otorhinolaryngology)
Abstract Introduction: Tracheoesophageal peristomal fistulae can often be solved by reducing the size of the fistula or replacing the prosthesis; however, even with conservative techniques, leakage around the fistula may continue in total laryngectomy patients. Also, several techniques have been developed to overcome this problem, including injections around the fistula, fistula closure with local flaps, myofascial flaps, or free flaps and fistula closure using a septal perforation silicon button. Objective: To present the results of the application of silicon ring expanding the voice prosthesis in patients with large and persistent peri-prosthetic fistula. Methods: A voice prosthesis was fitted to 42 patients after total laryngectomy. Leakage was detected around the prosthesis in 18 of these 42 patients. Four patients demonstrated improvement with conservative methods. Eight of 18 patients who couldn't be cured with conservative methods were treated by using primary suture closure and 4 patients were treated with local flaps. As silicon ring was applied as a primary treatment in the 2 remaining patients and also, applied to 2 patients who had recurrence after suture repair and to 2 patients who had recurrence after local flap implementation. Silicon rings were used in a total of 6 patients due to the secondary trachea-esophageal fistula. Patients were treated with provox-1 initially and later with provox-2. At the time of leakage around the fistula, 6 patients had provox-2. Results: Fistulae were treated successfully in 6 patients, and effective speech of patients was preserved. Patients experienced no adaptation problem. Prosthesis changing time was not different between silicon rings expanded and normal prosthesis applied patients. Silicon ring combined voice prosthesis was used 26 times; there was no recurrence in fistula complication during 29 ± 6 months follow up. Conclusion: Silicon rings for modified expanded voice prosthesis seems to be an effective treatment for persistent peri-prosthetic leakage, for both, fistula closure and preserving the patients speech.